1959
DOI: 10.1042/bj0730573
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose uptake by muscle. 3. The effects of insulin, anoxia, salicylate and 2:4-dinitrophenol on membrane transport and intracellular phosphorylation of glucose in the isolated rat heart

Abstract: In previous papers (Randle & Smith, 1958a, b) evidence was presented that insulin, anoxia and substances such as salicylate or 2:4-dinitrophenol, which inhibit oxidative phosphorylation, increase the uptake of glucose and D-xylose by isolated rat diaphragm by accelerating the transfer of these sugars across the muscle-cell membrane. The conclusion was drawn that the transfer process for sugars in muscle is inhibited by a substance generated during oxidative phosphorylation and that insulin activates the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
145
0
1

Year Published

1970
1970
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(163 citation statements)
references
References 10 publications
(4 reference statements)
17
145
0
1
Order By: Relevance
“…Since this is not observed, the inhibition of glycolysis by butyrate likely occurs before phosphorylation of glucose. These observations are in agreement with previous studies showing a decrease in the rate of glycolysis [1,2,4] and accumulation of free intracellular glucose [3] in the presence of butyrate. The results also suggest that the effects of iodoacetate on high-energy phosphate metabolism are reasonably specific.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Since this is not observed, the inhibition of glycolysis by butyrate likely occurs before phosphorylation of glucose. These observations are in agreement with previous studies showing a decrease in the rate of glycolysis [1,2,4] and accumulation of free intracellular glucose [3] in the presence of butyrate. The results also suggest that the effects of iodoacetate on high-energy phosphate metabolism are reasonably specific.…”
Section: Resultssupporting
confidence: 83%
“…Although the exact mechanism by which the presence of fatty acids inhibits glucose utilization is somewhat uncertain, the observed accumulation of glucose [3] in the heart when both glucose and fatty acids are provided in the medium suggests that the inhibition of glucose utilization occurs after glucose uptake but before the first phosphorylation event. "P-NMR spectroscopy of the Langendorff perfused rat heart can be used to follow changes in the concentrations of major pools of phosphorus-containing metabolites in vivo [5].…”
Section: Introductionmentioning
confidence: 99%
“…Also Morgan, Henderson, Regen & Park (1961) (1967) found that material accumulated by uptake2 washed out very readily, though this finding may not be capable of strict application to the trachea in which there is some retention of isoprenaline (Foster, 1969).…”
Section: The Effect Of Substrate Concentration On Metabolism Of (-)-Fmentioning
confidence: 99%
“…Hearts were excised rapidly, dropped into 0.9% NaCl (4°C), and mounted on a modified Langendorff perfusion apparatus. 18 For synthesis studies, preliminary perfusion was performed for 30 minutes with amino acid-rich "BGJ" solution (Grand Island Biological Co.) in Krebs-Henseleit buffer, containing 50 ;itg/ml bovine insulin (Sigma Chemical Co.), 15 nut glucose and 0.80 mM phenylalanine, and gassed with 95% O 2 + 5% CO 2 -The perfusion pressure was 65 mm Hg throughout the study, and beating rates were held constant at 350/min by atrial pacing. After the preliminary perfusion, the solution was changed to a similar one containing 0.80 mM [ 3 H]phenylalanine (1.3 X 10 6 dpm/ftmol).…”
Section: " 17mentioning
confidence: 99%